SOAPsplice: Genome-Wide ab initio Detection of Splice Junctions from RNA-Seq Data - Huang, Songbo; Zhang, Jinbo; Li, Ruiqiang; Zhang, Wenqian; He, Zengquan; Lam, Tak-Wah; Peng, Zhiyu; Yiu, Siu-Ming (Frontiers in Genetics, 2011)
RNA-Seq, a method using next generation sequencing technologies to sequence the transcriptome, facilitates genome-wide analysis of splice junction sites. In this paper, we introduce SOAPsplice, a robust tool to detect splice junctions using RNA-Seq data without using any information of known splice junctions. SOAPsplice uses a novel two-step approach consisting of first identifying as many reasonable splice junction candidates as possible, and then, filtering the false positives with two effective filtering strategies. In both simulated and real datasets, SOAPsplice is able to detect many reliable splice junctions with low false positive rate. The improvement gained by SOAPsplice, when compared to other existing tools, becomes more obvious when the depth of sequencing is low. SOAPsplice is freely available at http://soap.genomics.org.cn/soapsplice.html.